PEMANFAATAN PELAYANAN KB-MKJP OLEH PASANGAN USIA SUBUR KELOMPOK MASYARAKAT MISKIN DI KECAMATAN TEMBALANG KOTA SEMARANG - Pangestika, Windiana Wahyu; Sriatmi, Ayun; Winarni, Sri (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Population growth is the main problem of population in Indonesia. Indonesia’s TFR is 2,6 children, while the TFR of the poor communities is larger, 3 children. The goverment program to control the rate of population growth is Family Planning (KB) by encouraging the community to use the Long-Term Contraception Method (MKJP). Tembalang District is the region which has the lowest number of KB-MKJP participants in Semarang City, in 2015 coverage is 6,75%, in 2016 is 7,15% and 6,12% in 2017, this coverage is far from goverment target, 65,2%. The purpose of this study is to identify and analyze the factors related to the utilization of KB-MKJP services by Fertile Age Couples (PUS) in the poor communities. The type of this study is quantitative research with analytic survey design and cross sectional approach. The population is PUS in the poor communities, with 94 samples selected based on simple random sampling. The results of this study by using Rank Spearman test indicate that the related variables to the utilization of KB-MKJP services are the age (p value 0,047), the number of children alive (p value 0,000), the occupation (p value 0,004), believe in KB-MKJP (p value 0,000), knowledge of KB-MKJP (p value 0,034), access to health services (p value 0,000), and the necessity perception of KB MKJP (p value 0,001). The lack of PUS knowledge about KB-MKJP is one of the main factors in the utilization of KB-MKJP services for the low poor communities. Expansion of the reach family planning safaris and increasing promotion of KB-MKJP is needed to increasing the number of KB-MKJP utilization.